College essays that made a difference - Princeton Review (Firm) (New York : Random House, 2008)
Presents 123 essays by real-life applicants to colleges such as Harvard, Princeton, Amherst, MIT, Northwestern, and many more, with profiles of the students, application results, and tips from admissions professionals at thirteen top-rated universities.
Includes index.
Young Adult
Keywords: College applications -- United States; Exposition (Rhetoric); Universities and colleges -- United States -- Admission; College applications; Colleges and universities -- United States -- Entrance requirements; Rhetoric